2009
DOI: 10.1016/j.joca.2008.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Very rapid clearance after a joint bleed in the canine knee cannot prevent adverse effects on cartilage and synovial tissue

Abstract: Blood is cleared very rapidly from the canine knee joint, but already has adverse effects on both cartilage and synovial tissue within that short time span. This rapid clearance can play a role in the discrepancy between long-term in vitro and in vivo effects of blood-induced joint damage since more than 10% v/v blood present for at least 48 h is needed to induce long-term adverse effects in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 23 publications
5
50
0
1
Order By: Relevance
“…Four blood injections in the left knee were given in four successive days, because of the rapid clearance of blood from the canine joint in contrast to humans 14 . As previously shown, this results in a period of at least 4 days continuous blood exposure with at least 20% v/v blood and leads to mild progressive cartilage damage and synovitis over time mimicking HA 13,14 .…”
Section: Canine In Vivo Experimentsmentioning
confidence: 99%
“…Four blood injections in the left knee were given in four successive days, because of the rapid clearance of blood from the canine joint in contrast to humans 14 . As previously shown, this results in a period of at least 4 days continuous blood exposure with at least 20% v/v blood and leads to mild progressive cartilage damage and synovitis over time mimicking HA 13,14 .…”
Section: Canine In Vivo Experimentsmentioning
confidence: 99%
“…10 Even rapid clearance of a joint bleed in a canine knee in vivo resulted in reduced proteoglycan synthesis rates in exposed cartilage. 11 It also contributed to synovial changes, which caused proteoglycan release from healthy cartilage. 11 The mechanism by which chondrocytes become apoptotic after exposure to blood is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…11 It also contributed to synovial changes, which caused proteoglycan release from healthy cartilage. 11 The mechanism by which chondrocytes become apoptotic after exposure to blood is unclear. It has been suggested that hydrogen peroxide production by chondrocytes as a result of IL1b stimulation, in combination with hemoglobin-derived iron, causes an increase in free radical formation, which permanently damages chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, usual clinical practice allowed for a tacit, moderate degree of tolerance for sporadic intraarticular hemorrhages, based on the clinical observation that joints were able to tolerate an infrequent bleed with little or no harm. However, increasing knowledge on the pathophysiology of hemarthrosis in vitro and in vivo, as well as in clinical experiments, indicates that we need to move towards a more stringent policy with regards to the prevention of occasional and subclinical intraarticular hemorrhages [1][2][3].…”
mentioning
confidence: 99%